1999
DOI: 10.1034/j.1399-3054.1999.100201.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and kinetic properties of a castor bean seed acid phosphatase containing sulfhydryl groups

Abstract: An acid phosphatase (EC 3.1.3.2) has been identified and purified from castor bean (Ricinus communis L., IAC‐80) seed through sulphopropyl (SP)‐Sephadex, diethylaminoethyl (DEAE)‐Sephadex, Sephacryl S‐200, and Concanavalin A‐Sepharose chromatography. The enzyme was purified 2 000‐fold to homogeneity, with a final specific activity of 3.8 μkat mg−1 protein. The purified enzyme revealed a single diffuse band with phosphatase activity on nondenaturing polyacrylamide gel electrophoresis, at pH 8.3. The relative mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
1
24
0
4
Order By: Relevance
“…has been generally used in enzymatic systems in order to inactivate the reactions by binding to essential sulfhydryl groups located at or near the active site. In the case of acid phosphatases, we have previously reported that the enzyme purified from bovine kidney (Granjeiro et al 1997) and from castor bean seed (Granjeiro et al 1999) were inhibited 97 and 93% in the presence of 10 mM and 1 mM Cu 2? , respectively.…”
Section: Discussionmentioning
confidence: 98%
“…has been generally used in enzymatic systems in order to inactivate the reactions by binding to essential sulfhydryl groups located at or near the active site. In the case of acid phosphatases, we have previously reported that the enzyme purified from bovine kidney (Granjeiro et al 1997) and from castor bean seed (Granjeiro et al 1999) were inhibited 97 and 93% in the presence of 10 mM and 1 mM Cu 2? , respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous plant APases have been puri®ed and characterized (reviewed by Du et al 1994). Plant APases that have been recently examined include the enzyme from seeds (Kawarasaki et al 1996;Ferreira et al 1999;Granjeiro et al 1999;Roknabadi et al 1999), root nodules (Penheiter et al 1997), leaves (Staswick et al 1994), bulbs (Guo and Pesacreta 1997), and plumules (Guo and Roux 1995). The purple APases represent a distinct class of non-speci®c APase that contain binuclear metal centers (Vincent and Averill 1990;Klabunde and Krebs 1997;Schenk et al 1999;Oddie et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Acid phosphatases (EC 3.1.3.2), enzymes that catalyze the hydrolysis of a wide range of orthophosphate monoesters, are largely distributed in nature and have been studied in numerous organisms and tissues (Granjeiro et al, 1997;Ferreira et al, 1998aFerreira et al, , 1998bGranjeiro et al, 1999;Fernandes et al, 2003;Jonsson et al, 2007). The enzyme found in mammalian tissues occurs in multiple forms that differ in regard to molecular mass, substrate specificity and sensitivity to inhibitors (Granjeiro et al, 1997).…”
Section: Acid Phosphatase 341 Signaling Featuresmentioning
confidence: 99%